Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.3 - Real Numbers and Algebraic Expressions - Problem Set 2.3 - Page 69: 81



Work Step by Step

First, we simplify the expression: $-3a-1+7a-2$ =$-3a+7a-1-2$ =$4a-3$ We evaluate the expression by substituting the value of $a=0.9$ into the expression: $4a-3$ =$4(0.9)-3$ =$4(\frac{9}{10})-3$ =$\frac{36}{10}-3$ =$\frac{36-3(10)}{10}$ =$\frac{6}{10}$ =$0.6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.